Adsorption of the Color Pollutant onto NiO Nanoparticles Prepared by a New Green Method - Ali , Omar Sadiq; AL-Mammar, Dunya Edan (Iraqi Journal of Science, 2024)
Green synthesis methods have emerged as favorable techniques for the synthesis of nano-oxides due to their simplicity, cost-effectiveness, eco-friendliness, and non-toxicity. In this study, Nickel oxide nanoparticles (NiO-NPs) were synthesized using the aqueous extract of Laurus nobilis leaves as a natural capping agent. The synthesized NiO-NPs were employed as an adsorbent for the removal of Biebrich Scarlet (BS) dye from aqueous solution using adsorption technique. Comprehensive characterization of NiO-NPs was performed using various techniques such as atomic force microscopy (AFM), Fourier transform infrared (FTIR), X-ray diffraction (XRD), Brunauer-Emmett and Teller (BET) analysis, and scanning electron microscopy (SEM). Additionally, operational parameters including adsorbent weight, adsorption duration, temperature, pH value, and initial BS dye concentration were optimized for the adsorption process. Isotherm analysis indicated a better fit of the Langmuir model with equilibrium experimental data than the Freundlich model. The kinetic study revealed that the Pseudo-second-order (PSO) model was more suitable to represent the adsorption process compared to the Pseudo-first-order (PFO) kinetic model. Thermodynamic analysis encompassing the changes in Gibbs free energy (∆G˚), enthalpy (∆H˚), and entropy (∆S˚) unveiled that the adsorption of BS dye onto NiO-NPs was a spontaneous endothermic process with an increase in the randomness.